2017
DOI: 10.4328/jcam.5225
|View full text |Cite
|
Sign up to set email alerts
|

Serum transaminase elevation in Patients with rotavirus gastroenteritis

Abstract: Bu çalışmayı yapmaktaki amacımız rotavirüs akut gastroenteriti ile ortalama indiare skoru arasında ilişkiyi değerlendirmektir. Gereç ve Yöntem: Ocak-Temmuz 2016 tarihleri arasında gastroenterit tanısı alan ve hidrasyon amacıyla hastaneye yatırılan 1 ay-16 yaş arası çocuk hastalar çalışmaya alındı. Rotavirüs pozitif gastroenteriti olan hastalar RPGE, rotavirus negatif gastroenteriti olan hastalar RNGE ve basit cerrahi prosedür için çocuk cerrahisi servisine yatırılan hastalar ise kontrol grubu olarak değerlendi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…In the study of Erdogan et al, while ALT and AST values were higher in patients with positive Rotavirus test, no significant difference was found in terms of WBC, PLT, PCT, MPV and CRP values [30]. The results of our study were similar to those in the literature.…”
Section: Discussionsupporting
confidence: 89%
“…In the study of Erdogan et al, while ALT and AST values were higher in patients with positive Rotavirus test, no significant difference was found in terms of WBC, PLT, PCT, MPV and CRP values [30]. The results of our study were similar to those in the literature.…”
Section: Discussionsupporting
confidence: 89%
“…The prevalence was highly reported during the dry season [ 15 , 21 ], bottle-fed children [ 15 , 22 , 23 ], and children with group A blood type [ 15 , 24 , 25 ]. Moreover, laboratory investigations revealed a significantly high level of serum transaminase among children infected with rotavirus [ 26 , 27 , 28 ]. Among many studies conducted worldwide, it was found that rotavirus infected children have a high chance of developing dehydration as a complication, and thus, must be closely monitored [ 7 , 16 , 29 , 30 ].…”
Section: Causative Agents Of Agementioning
confidence: 99%
“…Amongst EIA kit used were Premier Rotaclone, Meridian Bioscience Inc., Cincinnati, OH, USA [ 10 , 11 , 12 , 19 , 93 , 94 ], RIDASCREEN Rotavirus R Biopharm AG, Darmstadt, Germany [ 15 , 93 ], and ProSpect Rotavirus Test, Oxoid Ltd., UK [ 22 , 93 ]. Rotavirus antigens can also be detected by using enzyme-linked immunosorbent assay (ELISA) [ 12 , 16 , 18 , 20 , 28 , 30 ] which includes ELISA kits such as Premier Rotaclone, Meridian Bioscience, Inc. [ 12 ], Fecal Rotavirus Antigen ELISA Kit (EDI, CA, USA) [ 16 ], ProSpecTM Rotavirus Microplate Assay, Oxoid [ 20 ] and Rota Antigen Test Device, Cambridge [ 28 ]. ELISA can also be used in the detection of rotavirus-specific IgM [ 29 ].…”
Section: Biomarkers In the Detection Of Common Aetiological Agents Of Agementioning
confidence: 99%